The Study of COVID-19's Perceptions as a Motivation to Exercise and Keep Fit Among Older Adults - Jiali Zhou MEd; Baoyuan Wu PhD; Fengyi Lu PhD; Xiujie Ma PhD (SAGE Publishing, 2023)
Since the end of 2019, a novel coronavirus pandemic (COVID-19), characterized by solid infectivity, rapid communication and diverse communication routes, has become widespread worldwide. This study investigates the motivations of older adults to exercise and keep fit due to the COVID-19 pandemic. The research is based on a survey of older adults in Chengdu, Sichuan Province, China. It adopts the event strength system theory as a conceptual framework and the stimulus-organism-response (S-O-R) theory for causal inferences. (1) the perception of COVID-19's novelty had a significant negative impact on older adults" intention to exercise and stay fit, and the perception of COVID-19's disruptiveness and criticality had a significant positive impact on older adults" intention to exercise and fitness; (2) The perception of COVID-19's novelty had a significant negative effect on risk cognition, and the disruptive and critical cognitions had a significant positive effect on risk perceptions; (3) risk perceptions had a prominent positive effect on older adults" intention to exercise and fitness; and (4) risk communication played an important moderating role between COVID-19 event strength cognition and older adults' intention to exercise and fitness. The study revealed that the perception of COVID-19's seriousness significantly impacted older adults" intentions to exercise and keep fit and that risk perception and communication acted as mediating factors.